PERSEPSI MASYARAKAT TERHADAP KEBERADAAN HUTAN MANGROVE DI DESA DUSUN BESAR KECAMATAN PULAU MAYA KABUPATEN KAYONG UTARA - Utami, Hilda Femilia; Muin, Sudirman; Dirhamsyah, M (JURNAL HUTAN LESTARI, 2020)
A coastal ecosystem that must be maintained as a provider of natural resources and as a life support system is called a mangrove forest. There is a connection between the society and the presence of mangrove forests that can not be separated which causes a public perception of the existence of mangrove forests. This study aims to examine the social perceptions of the existence of mangrove forests and analyze the relationship between the level of education, income level, and the level of dependence on mangrove forests with social perceptions of the existence of mangrove forests in Dusun Besar village, Pulau Maya District, North Kayong Regency. This study uses a survey method with interviews and questionnaires containing several questions asked to respondents, and data collected by using purposive random sampling. Data is analyzed by using descriptive analysis of the Chi-Square test and inferential analysis using nonparametric statistical tests of the Kendall Tau correlation. The number of respondents in this study is 92 people from 1.118 KK. The results of this study indicate that society perceptions tend to be positive (53,26%), low-income levels (55,43%), and high levels of dependency (54,35%). There is a positive and insignificant relationship between the level of education and perception (sig (2-tailed) amount of 0,697, the score of the correlation coefficient is 0,037). There is a positive and significant relationship between the level of income and perception (sig (2-tailed) amount of 0,031, the score of the correlation coefficient is 0,183), and there is a positive and significant relationship between the level of dependency and perception (sig (2-tailed) amount of 0,000, the score of the correlation coefficient is 0,420).Keywords: Dusun Besar Village, mangrove forest, perception.